The peacemaker [large type] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Mifflin County mystery, 2025)
"An Unresolved Mystery Holds an Amish Community in Limbo. In book two of A Mifflin County Mystery series, Rosa Petersheim's disappearance continues to cause suspicion and pain to swirl in the Big Valley. Ada's best friend, Rosa, disappeared a year ago and still has not been found. In their grief and confusion, Ada and Rosa's boyfriend, Ephraim, have grown very close. But some in the community feel Ephraim is responsible for Rosa's disappearance. Now Rosa's younger sister is making accusations against Ephraim that can't be true, and he pulls away from Ada, feeling betrayed. A fire set by an arsonist might finally be the thing to reveal secrets that have long been dividing this community of friends and family. But will it be too late for love between the peacemaker and the suspect?"--